Sovereignty in the Age of Radicalism: Political Theology and the State’s Battle Against Hizbut Tahrir in Indonesia - Pasqa, M (Candidate: Jurnal Sains Politik, 2024)
This study examines Indonesia’s counter-radicalism strategies against Hizbut Tahrir Indonesia (HTI) through the framework of Carl Schmitt’s political theology. HTI, a transnational Islamist group advocating for a global caliphate, poses a direct challenge to Indonesia’s pluralistic democracy and its foundational ideology, Pancasila. The Indonesian government’s response, including the 2017 ban on HTI under a Presidential Decree, highlights the state’s assertion of sovereignty as a "theological sovereign," a concept central to Schmitt’s idea of sovereignty as "the power to decide on the exception." This research explores how the state mobilizes Pancasila as a secularized theological construct to delegitimize HTI’s ideology and reinforce national unity. Legal, social, and collaborative strategies are critically evaluated, revealing the interplay between theological narratives and practical governance. Comparative insights from Malaysia and Turkey contextualize Indonesia’s unique approach, emphasizing its reliance on Pancasila as a unifying yet sacred framework. The findings reveal that while Indonesia’s measures effectively disrupt HTI’s organizational structure, they risk marginalizing dissent and narrowing democratic discourse. The state’s theological framing of Pancasila, while successful in addressing immediate threats, raises concerns about its implications for pluralism and freedom of expression. This study contributes to the broader understanding of political theology in addressing radical ideologies, offering valuable insights into the balance between sovereignty, national identity, and democratic governance. The Indonesian experience underscores the need for inclusive approaches that address the root causes of radicalization while preserving the democratic ideals that underpin pluralistic societies.